Test of Antioxidant and Vitamin C Levels in the Combination of Rose Tea (Rosa damascena Mill) and Lemon (Citrus limon L.) with Variations of Clay and Aluminum Frying Pans - Saniya Nurul Farika; Ambarwati (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2025)
Tea is a drink made from the shoots of the Camellia sinensis plant that has undergone certain processing processes such as wilting, grinding, enzymatic oxidation, and drying. The activity of drinking tea is a habit that has long been known to the Indonesian people. A study has been conducted on the antioxidant and vitamin C content test in a combination of rose tea and lemon with variations of clay and aluminum frying tools. The purpose of this study was to determine the antioxidant levels and vitamin C content in rose tea and lemon. This study used an experimental research type with a Completely Randomized Design (CRD) with one factor, namely frying variations with three replications. Antioxidant activity was measured by the free radical capture method with DPPH, while the vitamin C test used the Iodometric titration. The results of 2 samples showed that the highest antioxidant levels were found in the clay pot frying treatment. The data were analyzed using SPSS 28 software with the results of the prerequisite test with the normality test and the homogeneity of variances test, then an independent sample T-test was carried out showing a significant value of antioxidant and vitamin C levels with <0.005 so that it can be concluded that the difference in treatment has an effect or is significant on the antioxidant and vitamin C levels of rose and lemon tea.